Composite copper current collector and preparation method thereof
By doping nanometal active materials into the polymer and forming a copper layer on the polymer film by electroless plating, the problems of conductivity and energy consumption in the preparation of composite copper current collectors are solved, and low-cost and efficient composite copper is achieved. Current collector preparation improves product performance and production efficiency.
Patent Information
- Application Number
- CN202411247121.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
During the preparation process of composite copper current collector, the surface of the polymer film does not have electrical conductivity and cannot be prepared by one-step electroplating. The introduction of the physical vapor deposition process increases energy consumption and generates hole defects, resulting in low yield.
Doping nanometal active materials into the polymer, preparing a modified polymer film by bidirectional stretching, and forming a copper layer on both sides of it by electroless plating. Then, an antioxidant layer is prepared on the copper layer to achieve composite copper collection Preparation of fluid.
One-step electroless plating method is implemented to prepare composite copper current collectors, which reduces energy consumption and improves yield, shortens the process flow, and promotes the promotion and application of composite copper current collectors.
Smart Images

Figure BDA0005031094660000071 
Figure BDA0005031094660000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of current collectors, in particular to a composite copper current collector and a preparation method thereof. Background Art
[0002] At present, composite copper current collectors based on polymer films have received extensive attention and application in the new energy industry. The preparation process of the composite copper current collector is usually divided into two steps: first, a layer of copper is deposited on a polymer film (such as polypropylene, polyethylene, polyester, etc.) by physical vapor deposition (magnetron sputtering or evaporation) to prepare a composite copper current collector semi-finished product with a certain conductivity. Then, the composite copper current collector semi-finished product is further treated by electroplating to thicken the conductive copper layer, thereby preparing a composite copper current collector with conductivity. Compared with traditional current collectors (copper foil), composite copper current collectors based on polymer films have the characteristics of low cost, light weight, and good insulation of the inner polymer film layer. These characteristics enable the composite current collector to reduce the cost of the battery and increase the energy density of the battery when used in the battery, prevent short circuits between the positive and negative electrodes, and increase safety.
[0003] At present, the preparation of composite copper current collectors has the following problems: Since the surface of the polymer film is not conductive, the preparation of the composite current collector cannot be completed by a one-step electroplating method. To solve this problem, it is necessary to add a physical vapor deposition process before electroplating to deposit a conductive thin copper layer on the surface of the polymer film to complete the preparation of the composite copper current collector. However, the introduction of the physical vapor deposition process will increase energy consumption and lead to an increase in preparation costs. In addition, in the process of preparing the semi-finished composite current collector by magnetron sputtering, hole defects are easily generated, resulting in a low yield of the composite copper current collector.
[0004] Therefore, in view of the above problems, it is necessary to develop a new method for preparing a composite copper current collector, so as to prepare a low-cost composite copper current collector to promote the promotion and application of the composite copper current collector. Summary of the invention
[0005] The object of the present invention is to provide a composite copper current collector and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for preparing a composite copper current collector comprises the following steps:
[0008] Step S1: doping active materials into a polymer and biaxially stretching to prepare a modified polymer film; the active materials are one or more of carbon, cadmium sulfide, silver iodide, silver oxide, nickel oxide, conductive fiber, nickel, chromium, tin, nickel-chromium alloy, tin-nickel-copper alloy, lead-tin alloy, and palladium-copper alloy;
[0009] Step S2: using a chemical plating method to form copper layers on the upper and lower sides of the modified polymer film;
[0010] Step S3: preparing an anti-oxidation layer on the copper layer to obtain a composite copper current collector.
[0011] Preferably, the preparation method of the modified polymer film is as follows:
[0012] Step (1): melt extrusion: adding the polymer and the active material into a twin-screw extruder, heating, melting, and extruding to obtain a molten raw material;
[0013] Step (2): casting: casting the molten raw material onto a casting roller, and cooling and forming the molten raw material to obtain a casting;
[0014] Step (3): Stretching: The cast sheet is subjected to a biaxial stretching process to obtain a modified polymer film.
[0015] In the above technical solution, by introducing nano-metal active materials into the modified polymer film, active deposition sites can be provided for chemical copper plating, thereby promoting the chemical copper plating, and improving the bonding force between the chemical copper plating layer and the polymer film, thereby improving the adhesion and stability of the copper plating layer. At the same time, by adopting this technical solution, there is no need to carry out cumbersome pretreatment processes such as activation, sensitization and degumming during the chemical copper plating process. The modified polymer film can directly enter the chemical copper plating tank for chemical copper plating, which greatly shortens the process of chemical copper plating and improves production efficiency.
[0016] More optimally, the modified polymer membrane comprises the following raw materials: 90-99 wt % of polymer and 1-10 wt % of active material, calculated by mass percentage.
[0017] More optimally, the polymer is one or more of polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polypropylene (EPR), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyphenylene sulfide (PPS).
[0018] Preferably, the particle size of the active material is 10-100 nm.
[0019] Preferably, in step (1), the temperature of heating and melting is higher than the melting point of the polymer.
[0020] More optimally, in step (2), the process conditions for the cooling treatment are: the cooling medium is water, and the cooling temperature is 10-50°C.
[0021] More optimally, in step (3), the process conditions of the biaxial stretching process are: a stretching ratio of 2-6, a stretching temperature of 80-160° C., and a temperature lower than the melting point of the polymer.
[0022] Preferably, the modified polymer film has a thickness of 3-12 μm.
[0023] More optimally, in the chemical plating method, the main components of the chemical plating solution are: sodium pyrrolidine dithiocarbamate 0.08g / L-0.12g / L, benzyltriphenylphosphonium bromide 0.16g / L-0.24g / L, 2-(hydroxymethyl)thiophene 0.24g / L-0.36g / L, Cu 2+ 10g / L-15g / L, potassium sodium tartrate 18g / L-24g / L, EDTA 8g / L-12g / L, α,α-bipyridine 0.008g / L-0.012g / L, potassium ferrocyanide 0.02g / L-0.03g / L, formaldehyde 2.5g / L-3.5g / L, sodium hydroxide 6g / L-7g / L and sodium carbonate 3g / L-6g / L, pH=11-12.
[0024] More optimally, the process conditions of the chemical plating are: temperature 40-60°C, time 6-8min, and relative movement speed of the film 3-10m / min.
[0025] More optimally, the thickness of the copper layer is 500-2000 nm, preferably 700-1200 nm.
[0026] In the above technical solution, the copper layer is located on the upper and lower surfaces of the modified polymer film and functions as a conductor.
[0027] More optimally, the material of the anti-oxidation layer is one or more of copper chromate, copper chromite, and chromium oxide.
[0028] Preferably, the anti-oxidation layer is prepared by one or more of dip coating, physical vapor deposition and chemical vapor deposition.
[0029] More optimally, the thickness of the anti-oxidation layer is 5-100 nm, and the thickness of the anti-oxidation layer cannot exceed one tenth of the thickness of the copper layer.
[0030] In the above technical solution, the material and thickness of the anti-oxidation layer should be consistent. The main function of the anti-oxidation layer is to prevent the metal conductive layer from being chemically corroded or physically damaged. The thickness of the anti-oxidation layer cannot exceed one tenth of the thickness of the copper layer. If the protective layer is too thin, it will not be able to effectively play a protective role, while if the protective layer is too thick, it may affect the conductive performance. Therefore, the material and thickness of the protective layer need to be reasonably selected and controlled to ensure that its protective effect on the conductive layer is maximized.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The composite copper current collector and the preparation method thereof of the present invention realize the one-step method, i.e., the chemical plating method, to prepare the composite copper current collector, and solve the problems of high energy consumption and low yield rate caused by the physical vapor deposition process in the conventional preparation process of the composite copper current collector. Compared with the composite copper current collector prepared by the traditional method, the performance of the composite copper current collector prepared by the present invention is not reduced, which further promotes the promotion and application of the composite current collector. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] In this embodiment, the PP is Shanghai Petrochemical M800E; the nickel-chromium alloy has a particle size of 50 nm and a grade of Ni80Cr20.
[0035] Embodiment 1: A method for preparing a composite copper current collector, comprising the following process:
[0036] Step S1: doping active materials into the polymer and biaxially stretching to prepare a modified polymer film with a thickness of 4.5 μm;
[0037] Step S2: placing the modified polymer film in a plating solution (the main components of the chemical plating solution are: sodium pyrrolidine dithiocarbamate 0.08 g / L, benzyl triphenylphosphine bromide 0.16 g / L, 2-(hydroxymethyl)thiophene 0.24 g / L, Cu 2+ 10g / L, potassium sodium tartrate 18g / L, EDTA 8g / L, α,α-bipyridine 0.008g / L, potassium ferrocyanide 0.02g / L, formaldehyde 2.5g / L, sodium hydroxide 6g / L and sodium carbonate 3g / L, pH=12), using chemical copper plating process (temperature 40℃, time 6min, film relative movement speed 10m / min), copper layers are formed on the upper and lower sides of the modified polymer film respectively;
[0038] Step S3: preparing an anti-oxidation layer (the material is copper chromate) on the copper layer by a chemical vapor deposition method to obtain a composite copper current collector;
[0039] The preparation method of the modified polymer membrane is as follows:
[0040] Step (1): melt extrusion: using PP as a polymer and nickel-chromium alloy as an active material, 950 g of PP and 50 g of nickel-chromium are added into a twin-screw extruder, heated and melted (temperature is 165° C.), and extruded to obtain a molten raw material;
[0041] Step (2): casting: casting the molten raw material onto a casting roller, and forming the casting by cooling (the cooling medium is water, and the cooling temperature is 10° C.), to obtain a casting;
[0042] Step (3): Stretching: The cast sheet is subjected to a biaxial stretching process (stretching ratio of 2, stretching temperature of 80° C.) to obtain a modified polymer film.
[0043] Embodiment 2: A method for preparing a composite copper current collector, comprising the following process:
[0044] Step S1: doping active materials into the polymer and biaxially stretching to prepare a modified polymer film with a thickness of 4.5 μm;
[0045] Step S2: placing the modified polymer film in a plating solution (the main components of the chemical plating solution are: 0.10 g / L sodium pyrrolidine dithiocarbamate, 0.2 g / L benzyltriphenylphosphonium bromide, 0.3 g / L 2-(hydroxymethyl)thiophene, 2+ 12g / L, potassium sodium tartrate 20g / L, EDTA 10g / L, α,α-bipyridine 0.01g / L, potassium ferrocyanide 0.025g / L, formaldehyde 3g / L, sodium hydroxide 6.5g / L and sodium carbonate 5g / L, pH=11), using chemical copper plating process (temperature 45℃, time 7min, film relative movement speed 7m / min), copper layers are formed on the upper and lower sides of the modified polymer film respectively;
[0046] Step S3: preparing an anti-oxidation layer (the material is copper chromate) on the copper layer by a chemical vapor deposition method to obtain a composite copper current collector;
[0047] The preparation method of the modified polymer membrane is as follows:
[0048] Step (1): melt extrusion: using PP as a polymer and nickel-chromium alloy as an active material, 940 g of PP and 60 g of nickel-chromium are added into a twin-screw extruder, heated and melted (temperature is 165° C.), and extruded to obtain a molten raw material;
[0049] Step (2): casting: casting the molten raw material onto a casting roller, and forming the molten raw material by cooling (the cooling medium is water, and the cooling temperature is 20° C.) to obtain a casting;
[0050] Step (3): Stretching: The cast sheet is subjected to a biaxial stretching process (stretching ratio of 3, stretching temperature of 90° C.) to obtain a modified polymer film.
[0051] Embodiment 3: A method for preparing a composite copper current collector, comprising the following process:
[0052] Step S1: doping active materials into the polymer and biaxially stretching to prepare a modified polymer film with a thickness of 4.5 μm;
[0053] Step S2: placing the modified polymer film in a plating solution (the main components of the chemical plating solution are: 0.12 g / L sodium pyrrolidine dithiocarbamate, 0.24 g / L benzyltriphenylphosphonium bromide, 0.36 g / L 2-(hydroxymethyl)thiophene, 2+ 15g / L, potassium sodium tartrate 24g / L, EDTA 12g / L, α,α-bipyridine 0.012g / L, potassium ferrocyanide 0.03g / L, formaldehyde 3.5g / L, sodium hydroxide 7g / L and sodium carbonate 6g / L, pH=12), using chemical copper plating process (temperature 50℃, time 7min, film relative movement speed 6m / min), copper layers are formed on the upper and lower sides of the modified polymer film respectively;
[0054] Step S3: preparing an anti-oxidation layer (the material is copper chromate) on the copper layer by a chemical vapor deposition method to obtain a composite copper current collector;
[0055] The preparation method of the modified polymer membrane is as follows:
[0056] Step (1): melt extrusion: using PP as a polymer and nickel-chromium alloy as an active material, 930 g of PP and 70 g of nickel-chromium are added into a twin-screw extruder, heated and melted (temperature is 165° C.), and extruded to obtain a molten raw material;
[0057] Step (2): casting: casting the molten raw material onto a casting roller, and forming the casting by cooling (the cooling medium is water, and the cooling temperature is 30° C.), to obtain a casting;
[0058] Step (3): Stretching: The cast sheet is subjected to a biaxial stretching process (stretching ratio of 4, stretching temperature of 100° C.) to obtain a modified polymer film.
[0059] Embodiment 4: A method for preparing a composite copper current collector, comprising the following process:
[0060] Step S1: doping active materials into the polymer and biaxially stretching to prepare a modified polymer film with a thickness of 4.5 μm;
[0061] Step S2: placing the modified polymer film in a plating solution (the main components of the chemical plating solution are: 0.12 g / L sodium pyrrolidine dithiocarbamate, 0.24 g / L benzyltriphenylphosphonium bromide, 0.36 g / L 2(hydroxymethyl)thiophene, 2+15g / L, potassium sodium tartrate 24g / L, EDTA 12g / L, α,α-bipyridine 0.012g / L, potassium ferrocyanide 0.03g / L, formaldehyde 3.5g / L, sodium hydroxide 7g / L and sodium carbonate 6g / L, pH=12), using chemical copper plating process (temperature 55℃, time 8min, film relative movement speed 4m / min), copper layers are formed on the upper and lower sides of the modified polymer film respectively;
[0062] Step S3: preparing an anti-oxidation layer (the material is copper chromate) on the copper layer by a chemical vapor deposition method to obtain a composite copper current collector;
[0063] The preparation method of the modified polymer membrane is as follows:
[0064] Step (1): melt extrusion: using PP as a polymer and nickel-chromium alloy as an active material, 920 g of PP and 80 g of nickel-chromium are added into a twin-screw extruder, heated and melted (temperature is 165° C.), and extruded to obtain a molten raw material;
[0065] Step (2): casting: casting the molten raw material onto a casting roller, and forming the molten raw material by cooling (the cooling medium is water, and the cooling temperature is 40° C.) to obtain a casting;
[0066] Step (3): Stretching: The cast sheet is subjected to a biaxial stretching process (stretching ratio of 5, stretching temperature of 110° C.) to obtain a modified polymer film.
[0067] Embodiment 5: A method for preparing a composite copper current collector, comprising the following process:
[0068] Step S1: doping active materials into the polymer and biaxially stretching to prepare a modified polymer film with a thickness of 4.5 μm;
[0069] Step S2: placing the modified polymer film in a plating solution (the main components of the chemical plating solution are: 0.12 g / L sodium pyrrolidine dithiocarbamate, 0.24 g / L benzyltriphenylphosphonium bromide, 0.36 g / L 2(hydroxymethyl)thiophene, 2+ 15g / L, potassium sodium tartrate 24g / L, EDTA 12g / L, α,α-bipyridine 0.012g / L, potassium ferrocyanide 0.03g / L, formaldehyde 3.5g / L, sodium hydroxide 7g / L and sodium carbonate 6g / L, pH=12), using chemical copper plating process (temperature 60℃, time 8min, film relative movement speed 3m / min), copper layers are formed on the upper and lower sides of the modified polymer film respectively;
[0070] Step S3: preparing an anti-oxidation layer (the material is copper chromate) on the copper layer by a chemical vapor deposition method to obtain a composite copper current collector;
[0071] The preparation method of the modified polymer membrane is as follows:
[0072] Step (1): melt extrusion: using PP as a polymer and nickel-chromium alloy as an active material, 900 g of PP and 100 g of nickel-chromium are added into a twin-screw extruder, heated and melted (temperature is 165° C.), and extruded to obtain a molten raw material;
[0073] Step (2): casting: casting the molten raw material onto a casting roller, and forming the molten raw material by cooling (the cooling medium is water, and the cooling temperature is 50° C.) to obtain a casting;
[0074] Step (3): Stretching: The cast sheet is subjected to a biaxial stretching process (stretching ratio of 6, stretching temperature of 120° C.) to obtain a modified polymer film.
[0075] Comparative Example 1: A method for preparing a composite copper current collector, comprising the following process:
[0076] Compared with Example 5, no active material is added to the modified polymer membrane of Comparative Example 1, and other steps are the same as those of Example 5.
[0077] Comparative Example 2: A method for preparing a composite copper current collector, comprising the following process:
[0078] The preparation method of the modified polymer membrane is as follows:
[0079] Step (1): melt extrusion: using PP as a polymer and nickel-chromium alloy as an active material, 800 g of PP and 200 g of nickel-chromium are added into a twin-screw extruder, heated and melted (temperature is 165° C.), and extruded to obtain a molten raw material;
[0080] Step (2): casting: casting the molten raw material onto a casting roller, and forming the molten raw material by cooling (the cooling medium is water, and the cooling temperature is 50° C.) to obtain a casting;
[0081] Step (3): stretching: the cast sheet is subjected to a biaxial stretching process (stretching ratio of 6, stretching temperature of 120° C.) to obtain a modified polymer film;
[0082] Compared with Example 5, the modified polymer membrane of Comparative Example 2 includes the following raw materials: 80 wt % of polymer and 20 wt % of active material, by mass percentage. Other steps are the same as those of Example 5.
[0083] Experiment: Binding strength test: The binding strength between the modified polymer film obtained in Examples 1-5 and Comparative Examples 1-2 and the copper layer was tested. After the copper layer was baked at 150°C for 3 minutes, a 3M tape was used to perform a sticky-off test, that is, the 3M tape was pasted on the copper layer and then quickly torn off. By observing whether the tape fell off, the binding strength between the modified polymer film and the copper layer can be evaluated.
[0084] Resistance test before plating: Take the modified polymer films obtained in Examples 1-5 and Comparative Examples 1-2, place them on a sample table, and test the sheet resistance of the samples using a four-probe sheet resistance meter.
[0085] Sheet resistance test: The composite copper current collectors obtained in Examples 1-5 and Comparative Examples 1-2 were placed on a sample stand, and the sheet resistance of the samples was tested using a four-probe sheet resistance meter.
[0086] Test Results
[0087]
[0088]
[0089] According to the data in the above table, we can clearly draw the following conclusions:
[0090] 1. Compared with Comparative Example 2, the pre-plating resistance of the modified polymer films of Examples 1-5 is very high, and the conductivity cannot be measured. This shows that when the content of active material in the modified polymer film is low, the material conductivity condition cannot be achieved without subsequent copper plating treatment, which ensures the insulation of the non-metallic layer in the middle of the composite current collector. Therefore, only when copper plating is performed later, the performance of the film will undergo a qualitative change, thereby achieving the conductive condition.
[0091] 2. Compared with Examples 1-5, there is almost no copper deposition on the surface of the composite copper current collector of Comparative Example 1, and the square resistance is very high. This is because without adding active materials, the modified polymer film lacks the active deposition sites required for chemical copper plating. Therefore, the surface of the modified polymer film cannot provide enough conductive sites and cannot effectively adsorb copper ions for deposition. At the same time, since enough copper cannot be deposited on the surface of the film, the surface resistance of the film is very high and the conductive performance is poor.
[0092] 3. Compared with Examples 1-5, the square resistance of the composite copper current collector of Comparative Example 2 decreases. It can be seen that when the content of active material in the modified polymer film is too high, the intermediate polymer film layer has conductivity, which does not meet the requirements of the intermediate polymer film layer of the composite current collector itself, and cannot prevent the positive and negative electrodes from short-circuiting and increase safety. Therefore, when preparing the modified polymer film, a mass ratio within the said range should be selected to ensure that the bonding force and insulation performance between the modified polymer film and other layers meet the requirements of the composite current collector.
[0093] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0094] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite copper current collector, characterized in that: The steps include: Step S1: doping active materials into a polymer and biaxially stretching to prepare a modified polymer film; the active materials are one or more of carbon, cadmium sulfide, silver iodide, silver oxide, nickel oxide, conductive fiber, nickel, chromium, tin, nickel-chromium alloy, tin-nickel-copper alloy, lead-tin alloy, and palladium-copper alloy; Step S2: using a chemical plating method to form copper layers on the upper and lower sides of the modified polymer film; Step S3: preparing an anti-oxidation layer on the copper layer to obtain a composite copper current collector.
2. The method for preparing a composite copper current collector according to claim 1, characterized in that: The preparation method of the modified polymer film is as follows: Step (1): melt extrusion: adding the polymer and the active material into a twin-screw extruder, heating, melting, and extruding to obtain a molten raw material; Step (2): casting: casting the molten raw material onto a casting roller, and forming the casting through cooling treatment to obtain a casting; Step (3): Stretching: The cast sheet is subjected to a biaxial stretching process to obtain a modified polymer film.
3. The method for preparing a composite copper current collector according to claim 2, characterized in that: The modified polymer membrane comprises the following raw materials: 90-99 wt % of polymer and 1-10 wt % of active material, calculated by mass percentage.
4. The method for preparing a composite copper current collector according to claim 3, characterized in that: The polymer is one or more of polypropylene, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, and polyphenylene sulfide.
5. The method for preparing a composite copper current collector according to claim 2, characterized in that: In the step (2), the process conditions for the cooling treatment are: the cooling medium is water, and the cooling temperature is 10-50°C.
6. The method for preparing a composite copper current collector according to claim 2, characterized in that: In the step (3), the process conditions of the biaxial stretching process are: the stretching ratio is 2-6, the stretching temperature is 80-160° C., and the temperature is lower than the melting point of the polymer.
7. The method for preparing a composite copper current collector according to claim 1, characterized in that: The thickness of the copper layer is 500-2000nm.
8. The method for preparing a composite copper current collector according to claim 1, characterized in that: The material of the anti-oxidation layer is one or more of copper chromate, copper chromite and chromium oxide.
9. The method for preparing a composite copper current collector according to claim 1, characterized in that: The preparation method of the anti-oxidation layer is one or more of dip coating, physical vapor deposition and chemical vapor deposition.
10. The method for preparing a composite copper current collector according to claim 1, characterized in that: The thickness of the anti-oxidation layer is 5-100 nm, and the thickness of the anti-oxidation layer cannot exceed one tenth of the thickness of the copper layer.
Citation Information
Cited By
Preparation method of functional current collector containing tin-cadmium alloy, functional current collector containing tin-cadmium alloy, and secondary battery
CN120127153A
Composite copper current collector and preparation method therefor
WO2026051446A1
